Secondary prevention among uninsured stroke patients: A free clinic study. (October 2020) - MacDonald, Madeline R; Zarriello, Sydney; Swanson, Justin; Ayoubi, Noura; Mhaskar, Rahul; Mirza, Abu-Sayeef
Objectives: Free clinics manage a diversity of diseases among the uninsured. We sought to assess the medical management of stroke in a population of uninsured patients. Methods: A retrospective chart review was conducted to collect chronic disease statistics from 6558 electronic medical records and paper charts at nine free clinics in Tampa, Florida, from January 2016 to December 2017. Demographics and risk factors were compared between stroke patients and non-stroke patients. Medication rates for several comorbidities were also assessed. Results: Two percent (107) of patients had been diagnosed with a stroke. Stroke patients were older (mean (M) = 56.0, standard deviation (SD) = 11.2) than the rest of the sample (M = 43.3, SD = 15.4), p < 0.001 and a majority were men (n = 62, 58%). Of the stroke patients with hypertension (n = 79), 81% (n = 64) were receiving anti-hypertensive medications. Of the stroke patients with diabetes (n = 43), 72% (n = 31) were receiving diabetes medications. Among all stroke patients, 44% were receiving aspirin therapy (n = 47). Similarly, 39% of all stroke patients (n = 42) were taking statins. Conclusions: Uninsured patients with a history of stroke may not be receiving adequate secondary prevention highlighting the risk and vulnerability of uninsured patients. This finding identifies an area for improvement in secondary stroke prevention in free clinics.